The Federal Democratic Republic of Ethiopia : Requests for Purchasing under the Rapid Financing Instrument, Debt Relief under the Catastrophe Containment and Relief Trust, Rephasing of Access Under the Three-Year Arrangements under the Extended Credit Facility and the Extended Fund Facility, and Reduction of Access under the Extended Fund Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. (IMF Staff Country Reports; Country Report, 2020)
This paper focuses on The Federal Democratic Republic of Ethiopia's Requests for Purchasing Under the Rapid Financing Instrument (RFI), Debt Relief Under the Catastrophe Containment and Relief Trust, Rephasing of Access Under the Three-Year Arrangements Under the Extended Credit Facility and the Extended Fund Facility, and Reduction of Access Under the Extended Fund Facility Arrangement. Ethiopia is facing a pronounced economic slowdown and an urgent balance of payments need owing to the coronavirus disease 2019 (COVID-19) pandemic. The authorities have taken strong actions to contain the health impact by implementing a mandatory 14-day quarantine for travelers entering the country, improving testing and containment capacity, strengthening epidemic response coordination and adopting a state of emergency to limit movement and gatherings and facilitate social distancing. Ethiopia showed good progress under the extended arrangements with the IMF, which aim to address external vulnerabilities and transition to a private sector-led growth model. The authorities remain committed to the reform program. The IMF staff supports the authorities' plan to accommodate COVID-related fiscal measures, and to resume the fiscal adjustment when the crisis subsides. In order to contain the upward pressure on public debt, the authorities should consider further tightening the spending envelope for state-owned enterprises not directly engaged in the COVID-19 emergency response.